2016
DOI: 10.3390/ijms17111942
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Function of the Tumor Suppressor p53 in Host Immune Response and the Tumor Microenvironment

Abstract: The tumor suppressor p53 is the most frequently mutated gene in human cancers. Most of the mutations are missense leading to loss of p53 function in inducing apoptosis and senescence. In addition to these autonomous effects of p53 inactivation/dysfunction on tumorigenesis, compelling evidence suggests that p53 mutation/inactivation also leads to gain-of-function or activation of non-autonomous pathways, which either directly or indirectly promote tumorigenesis. Experimental and clinical results suggest that p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 138 publications
6
77
0
1
Order By: Relevance
“…Numerous lines of evidence indicate that tumor microenvironment could alter myeloid cells (macrophages, dendritic cells, and granulocytes) and make them become potent immunosuppressive cells. 68, 69 Tumor-associated macrophages contribute to tumor survival and invasion by secreting cytokines and chemokines, 70 as well as maintaining pro-tumor inflammation. 68, 69 Tumor associated dendritic cells have serious functional deficits and cause cancer immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous lines of evidence indicate that tumor microenvironment could alter myeloid cells (macrophages, dendritic cells, and granulocytes) and make them become potent immunosuppressive cells. 68, 69 Tumor-associated macrophages contribute to tumor survival and invasion by secreting cytokines and chemokines, 70 as well as maintaining pro-tumor inflammation. 68, 69 Tumor associated dendritic cells have serious functional deficits and cause cancer immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, miR-29b could upregulate the level of p53 [40], and consequently activate downstream the p53 pathway including caspases 3 and 8, which eventually induce the apoptosis of tumor cells [45]. In addition, the development of tumors often accompanies chronic inflammation and oxidant stress [46], and thus, the inflammatory cytokines and oxidant enzymes also play a significant role in tumor development. The normal activities of oxidant enzymes (MPO, MDA) could promote cell proliferation; however, the abnormal expression would upregulate the expression of p53 and miR-29b, inducing cell apoptosis [47].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cytokines also play a pivotal role in the procession and metastasis in the tumor, whereby the excess inflammatory factors would upregulate the miR-29b, p53, and caspases 3 and 8 levels to stimulate the tumor cell apoptosis [47,48,49]. Cui et al [46] demonstrated that the expression of p53 was upregulated in inflamed tissues, and then, p53 negatively regulated the pro-inflammatory factors. Moreover, the pro-inflammatory factors stimulated the expression of miR-29b and enhanced the anti-tumor effect mediated by enhancing the cell apoptosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor therapy strategies based on p53 activation are focused on tumor cell apoptosis and cell cycle arrest to protect from tumorigenesis or metastasis [20]. Recent compelling evidence indicates that p53 plays a crucial role in tumor suppression through regulating immune surveillance in the tumor microenvironment (TME) [21]. Meanwhile, elevated p53 is detected in contexts of chronic inflammation, autoimmune diseases and virus infections, including inflammatory bowel disease, rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and HIV infection [22].…”
Section: Discussionmentioning
confidence: 99%